Gustavus Adolphus a history of the art of war from its revival after the middle ages to the end of the Spanish succession war, with a detailed account of the campaigns of the great Swede, and of the most famous campaign of Turenne, Condé, Eugene and Marlborough. With 237 charts, maps, plans of battles and tactical manoeuvres, cuts of uniforms, arms, and weapons - Dodge, Theodore Ayrault (Boston Mifflin and company, 1895)
This work has been selected by scholars as being culturally important, and is part of the knowledge base of civilization as we know it. This work was reproduced from the original artifact, and remains as true to the original work as possible. Therefore, you will see the original copyright references, library stamps (as most of these works have been housed in our most important libraries around the world), and other notations in the work.
Keywords: Gustav II Adolf, King of Sweden, 1594-1632.